A Phase I, Dose-Escalation Trial of Pazopanib in Combination with Cisplatin in Patients with Advanced Solid Tumors: A UNICANCER Study. Issue 2 (December 2016) - Diéras, Véronique; Bachelot, Thomas; Campone, Mario; Isambert, Nicolas; Joly, Florence; Tourneau, Christophe; Cassier, Philippe; Bompas, Emmanuelle; Fumoleau, Pierre; Noal, Sabine; Orsini, Christine; Jimenez, Marta; et al.
Abstract Introduction To determine the feasibility, maximum-tolerated dose (MTD), and dose-limiting toxicities (DLT) of pazopanib in combination with cisplatin. Methods Patients with advanced malignancies were included in a 3 + 3 dose-escalation phase I study. Pazopanib administration started 8 days before the first infusion of cisplatin; some patients were treated according to a reverse sequence (cisplatin first). Five dose levels (DLs) were planned. MTD was based on DLT observed during cycles 1 and 2. Results Thirty-five patients were enrolled. The MTD was reached at the first DL, (pazopanib 400 mg daily + cisplatin 75 mg/m2 every 21 days). Main DLTs were pulmonary embolism, neutropenia, thrombocytopenia, and elevation of liver enzymes. Overall, most common adverse events were anemia (83%), fatigue (80%), thrombocytopenia (80%), neutropenia (73%), hypertension (59%), neurotoxicity (56%), and anorexia (53%). Sixteen patients (46%) discontinued the study due to toxicity. One patient (sarcoma) had a complete response, and three patients (one with breast cancer and two with ovarian cancers) had a partial response. Pharmacokinetic (PK) analyses showed interactions with aprepitant, resulting in increased exposure to pazopanib, which might explain partly the poor tolerance of the combination. Conclusion Cisplatin and pazopanib could not be administered at their single agent full doses, partly due to a PK interaction between pazopanib and aprepitant. Funding This work was funded by GlaxoSmithKline and by the charity Ligue Nationale de Lutte Contre le Cancer. Trial registered ClinicalTrials.gov identifier, NCT01165385.